Situational Analysis of Road Traffic Accidents- A case of Madurai District rural areas, Tamil Nadu - Akkayasamy, Vigneshwaran Subbiah; Panneer, Sigamani (Indian Journal of Community Health, 2020)
Background: Road traffic accidents (RTAs) have emerged as a major public health concern due to the growing number of motorized vehicles all over the world. In India, the burden of road traffic accidents is increasing and from 1991 to 2011, the number of fatal deaths has more than doubled. Madurai district is among road accident-prone regions of the state of Tamil Nadu. Objective: This paper aims to examine and understand trends and patterns of RTAs in rural areas of Madurai District between 2014-2018. Methods: The researchers collected RTAs data from Madurai District Crime Records Bureau. we have considered time-series data from 2014 to 2018 and the number and percentage of deaths by the distribution of relevant factors such as timing, gender, road type, and vehicles to understand holistic patterns of RTAs. Results: Totally 9950 road accidents were reported by Madurai District Crime Records Bureau between 2014 and 2018 and on an average over 1990 accidents have occurred every year. Nearly 40 per cent fatal accidents occurred between 15-21 h. Men were the victims in 87 per cent of deaths and men died 6.8 times higher than females during 2014-2018. Over 57 per cent of fatalities have occurred in National Highways. The proportion of two-wheelers contributed to road deaths is 28 per cent and two-wheelers caused maximum road deaths than other vehicles. Conclusion: The study shows a decreasing trend in road accidents and fatalities in Madurai district. However, a significant number of men dying in road accidents highlights the difficulties of their families.